2022
DOI: 10.3389/fphar.2022.851589
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review of Flavone Isomers Apigenin and Genistein in Prostate Cancer Treatment

Abstract: The initial responses to standard chemotherapies among prostate cancer (PCa) patients are usually significant, while most of them will finally develop drug resistance, rendering them with limited therapies. To discover new regimens for the treatment of PCa including resistant PCa, natural products, the richest source of bioactive compounds, can serve as a library for screening and identifying promising candidates, and flavones such as apigenin and genistein have been used in lab and clinical trials for treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 102 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…Isoflavonoids such as daidzin and genistin, as well as flavonoid apigenin, were found in all soy parts. Such metabolites were related to potential bioactive properties against cancer and anti-inflammatory capacity ( 7 , 73 75 ). Moreover, bioactive isoflavonoids, such as formononetin 7-O-glucoside (ononin) and biochanin A 7-O-glucoside (astroside), were identified in at least one soy by-product.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavonoids such as daidzin and genistin, as well as flavonoid apigenin, were found in all soy parts. Such metabolites were related to potential bioactive properties against cancer and anti-inflammatory capacity ( 7 , 73 75 ). Moreover, bioactive isoflavonoids, such as formononetin 7-O-glucoside (ononin) and biochanin A 7-O-glucoside (astroside), were identified in at least one soy by-product.…”
Section: Resultsmentioning
confidence: 99%
“…Genistein is an isoflavone primarily identified in Glycine max (soybean) extract, among many other sources, such as peanuts, green peas, and legumes. Genistein reportedly prevents various diseases, such as anti-inflammatory, reducing osteoporosis, improving obesity, and anti-tumor ( Fuloria et al, 2022 ; Goh et al, 2022 ; Ji et al, 2022 ). Wang et al found that genistein can activate the Nrf2-mediated antioxidant defense system in NP cells ( Wang et al, 2019 ) and subsequently inhibit TBHP-induced apoptosis and ECM degradation.…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…Similarly, the anti-cancer activity of genistein has been also comprehensively reviewed ( Hou, 2022 ). Genistein exhibits cytotoxicity to many cancers, such as breast cancer ( Pawlicka and Filip, 2022 ), prostate cancer ( Ji et al, 2022 ), liver cancer ( Zhang et al, 2019 ), and kidney cancer ( Imai-Sumida et al, 2020 ). In mammalians, isoflavones, such as genistein, can exhibit estrogen-like biological functions, due to the structural similarity between genistein and estrogen.…”
Section: Introductionmentioning
confidence: 99%